2015
DOI: 10.1177/1028315315623055
|View full text |Cite
|
Sign up to set email alerts
|

Motivations, Expectations, and Experiences of Expatriate Academic Staff on an International Branch Campus in China

Abstract: This article explores the experiences of non-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 26 publications
(40 reference statements)
0
73
1
Order By: Relevance
“…Bhandari and Blumenthal 2011;Brooks 2017;Guruz 2011;Krzaklewska 2008). Fewer studies explore mobility and opportunity structures in relation to academics (Ackers 2008;Bedenlier and Zawacki-Richter 2015;Bönisch-Brednich 2016;Cai and Hall 2015;Fahey and Kenway 2010;Hoffman 2009;Kim 2008Kim , 2009aKim , 2009bKim , 2010Kim , 2017Kim and Locke 2010;Musselin 2004;Pherali 2012). Kim and Locke (2010) and ECU (2014) call for qualitative studies to uncover the stories behind the sparse statistics.…”
Section: Introduction: Mobility As the New Capital In The Global Knowmentioning
confidence: 99%
“…Bhandari and Blumenthal 2011;Brooks 2017;Guruz 2011;Krzaklewska 2008). Fewer studies explore mobility and opportunity structures in relation to academics (Ackers 2008;Bedenlier and Zawacki-Richter 2015;Bönisch-Brednich 2016;Cai and Hall 2015;Fahey and Kenway 2010;Hoffman 2009;Kim 2008Kim , 2009aKim , 2009bKim , 2010Kim , 2017Kim and Locke 2010;Musselin 2004;Pherali 2012). Kim and Locke (2010) and ECU (2014) call for qualitative studies to uncover the stories behind the sparse statistics.…”
Section: Introduction: Mobility As the New Capital In The Global Knowmentioning
confidence: 99%
“…Visiting scholars "do not receive adequate preparation prior to their departure" from their origin country (Cai & Hall, 2016). Furthermore, the "implications of this unpreparedness may mean a reduction in intercultural competence" which in turn will impact cultural adjustment to the host country (Gopal's 2011 research as cited in Cai and Hall, 2016, p. 250).…”
Section: Resultsmentioning
confidence: 99%
“…These include self-efficacy (Bandura, 1977), openness to new experiences, an interest in world languages, and cross-cultural competence. Furthermore, to ease the acculturalization process, Cai and Hall (2016) suggest that it is highly recommended that sojourners receive pre-departure support for living in the new environment that are specific to the situation in which they will find themselves in the host country.…”
Section: Acculturating To a Host Countrymentioning
confidence: 99%
“…These institutions have had mixed success. For example, Cai and Hall (2016) found that, although staff found many benefits from working on an international branch campus, they were insufficiently prepared for the structural and cultural differences inherent in working as an academic in China. The authors argue that university level discourse, communicated through policy and marketing texts, which promotes the vision of a diverse international university community, means not enough attention is being paid to the structural, political and cultural differences inherent in working as an academic in China.…”
Section: Internationalisation Of Higher Education In Chinamentioning
confidence: 99%